Fugitive saints : Catholicism and the politics of slavery - Grimes, Katie Walker (Fortress Press, 2017)
"How should the Catholic Church remember the sins of its saints? This question proves particularly urgent in the case of those saints who were canonized due to their relation to black slavery. Today, many of their racial virtues seem like racial vices. This book proposes black fugitivity, as both a historical practice and an interpretive principle, to be a strategy by which the church can build new hagiographical habits. Rather than searching inside itself for racial heroes, the church should learn to celebrate those black fugitives who sought refuge outside of it."--Back cover.